2006
DOI: 10.1111/j.0902-4441.2006.t01-1-ejh2553.x
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation of cyclin D2 by juxtaposition with T‐cell receptor alpha/delta locus in t(12;14)(p13;q11)‐positive childhood T‐cell acute lymphoblastic leukemia

Abstract: We have confirmed, in two additional cases, that the recurrent T-ALL-associated t(12;14) results in overexpression of cyclin D2. The t(12;14) is the first neoplasia-associated translocation shown to result in overexpression of cyclin D2. Furthermore, it is the first example of a T-cell neoplasm with a targeted deregulation of a member of a cyclin-encoding gene family.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…From a molecular perspective, Xq22 and 12p13 were juxtaposed with the TCR α/δ loci (14q11). Breakpoints within the TCR α/δ locus occur in more than 20% of T-ALL cases with abnormal karyotypes, and the mechanism underlying these translocations most likely involves illegitimate V(D)J recombination [4, 12, 13]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From a molecular perspective, Xq22 and 12p13 were juxtaposed with the TCR α/δ loci (14q11). Breakpoints within the TCR α/δ locus occur in more than 20% of T-ALL cases with abnormal karyotypes, and the mechanism underlying these translocations most likely involves illegitimate V(D)J recombination [4, 12, 13]. …”
Section: Discussionmentioning
confidence: 99%
“…T-ALL is a genetically heterogeneous disease with translocations that usually involve recombination between T-cell receptor ( TCR ) loci and several different partner genes [3]. Most of these translocations result in deregulation of the partner genes that are located near TCR regulatory elements [4]. The most common partner genes are HOX11 , HOX11L2 , MYC , and TAL1 .…”
Section: Introductionmentioning
confidence: 99%
“…Loss of 9p material was seen in close to 20% of the cytogenetically abnormal CNS, central nervous system; F, female; M, male; pEFS, probability of event-free survival (5 years); pOS, probability of overall survival (5 years); WBC, white blood cell. (Karrman et al, 2006) CNS, central nervous system; F, female; M, male; WBC, white blood cell; þ, alive at last follow-up. cases (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, five cases had breaks at 8p21 and four cases had breaks at 12p13 (Table SI: cases 47, 62, 68, 69, 74, 77, 78, 79 and 90). Various genes localized to band 12p13 have been associated with rearrangements in T-cell malignancies, including ETV6 in PTCL (Yagasaki et al, 2001) and CCND2 with over-expression in T-cell acute lymphoblastic leukemia (ALL) (Karrman et al, 2006). High level amplifications of 12p13 have also been detected by CGH in three PTCL-US cases (Zettl et al, 2004) and a recent study using a cDNA microarray reported a PTCL-US subgroup with a gene expression signature including over-expression of CCND2 (Ballester et al, 2006).…”
Section: Discussionmentioning
confidence: 99%